Salmerón-Sánchez , E., Fuertes Aguilar, J., Španiel, S., Mendoza-Fernández, A. J., Martínez-Hernández, F. & Mota, J. F. (2016) The status of Hormathophylla baetica: a new combination and lectotypification in Hormathophylla cochleata. Phytotaxa 280 (1): 45–54. - Salmerón-Sánchez, Esteban; Aguilar, Javier Fuertes; Španiel, Stanislav; Mendoza-Fernández, Antonio Jesús; Martínez-Hernández, Fabián; Mota, Juan F. (Phytotaxa, 2016)
N/A